Performance of New and Old Short-Seasoned Arachis Hypogea (Groundnut) Varieties Under Same Agronomic Practices - Cosmas Parwada; Sandra Zhuwao; Ronald Mandumbu; Handsen Tibugari; Savemore Ngirazi (Journal of Agronomy Research, 2020)
Performance of three newly released short-seasoned (Nsinjiro, Chitala and JL11) were evaluated against old (Nyanda, Illanda and Tern) groundnuts varieties under same agronomic practices. A field experiment laid in a randomized complete block design (RCBD) with three replicates was done. Varieties were evaluated for days to 50% emergence, 50% flowering, days to physiological maturity, pod and seed yield, and shelling percentage. There were no significant difference in the days to 50% emergence among all varieties but significant difference (p ˂ 0.05) were observed on days to 50% flowering. JL11 and Tern took shortest (90 days) and longest (120 days) time to physiological maturity respectively. Chitala had highest (3.804t/ha) and Tern had lowest (3.020t/ha) seed yield. Jl11 had highest (83%) and Nyanda least (68%) shelling percentage. Results showed that the new varieties out-performed the old varieties in all measured parameters. Therefore, resource constrained farmers may safely opt for the new short-seasoned varieties over the old ones.
Keywords: Adaptation